Sub-gradient algorithms for solving multi-dimensional analysis problems of dissimilarity data - Yassine, Adnan (Zielona Góra: Uniwersytet Zielonogórski)
The multi-dimensional scaling (MDS) problem, extensively addressed in data analysis, has been investigated in significant works (e.g. De Leeuw, 1977; 1988; De Leeuw and Pruzansky, 1976; Kruskal, 1964; Shepard, 1974). It consists in determination of a configuration x* such that the matrix elements of distances between the points are required to be those of a given matrix called the proximity or dissimilarity matrix or, if this is impossible, it reduces to the nearest optimization problem in which a function (called the loss function) is to be minimized.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka